2021
DOI: 10.1186/s40170-021-00272-7
|View full text |Cite
|
Sign up to set email alerts
|

Robust metabolic transcriptional components in 34,494 patient-derived cancer-related samples and cell lines

Abstract: Background Patient-derived bulk expression profiles of cancers can provide insight into the transcriptional changes that underlie reprogrammed metabolism in cancer. These profiles represent the average expression pattern of all heterogeneous tumor and non-tumor cells present in biopsies of tumor lesions. Hence, subtle transcriptional footprints of metabolic processes can be concealed by other biological processes and experimental artifacts. However, consensus independent component analyses (c-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Assessing EMT state in patient‐derived samples is technically difficult due to its dynamic nature (Vasaikar et al , 2021) and a similar level of technical limitations also exists in detecting and quantifying the global altered metabolic state in tumors (Han et al , 2021; Rohatgi et al , 2022). Nevertheless, transcriptomic approaches can effectively portrait the metabolic reprogramming in cancer as the metabolic enzyme regulation also occurs at the transcriptional level (Leeuwenburgh et al , 2021; Rohatgi et al , 2022). On this basis, the present study conducted a comprehensive lung cancer transcriptome analysis in the context of EMT‐associated metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing EMT state in patient‐derived samples is technically difficult due to its dynamic nature (Vasaikar et al , 2021) and a similar level of technical limitations also exists in detecting and quantifying the global altered metabolic state in tumors (Han et al , 2021; Rohatgi et al , 2022). Nevertheless, transcriptomic approaches can effectively portrait the metabolic reprogramming in cancer as the metabolic enzyme regulation also occurs at the transcriptional level (Leeuwenburgh et al , 2021; Rohatgi et al , 2022). On this basis, the present study conducted a comprehensive lung cancer transcriptome analysis in the context of EMT‐associated metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…The search for novel anti-cancer metabolic targets has significantly benefited from recent developments in characterization of large panels of diverse cancer cell lines, including their genetic dependency maps, genomic, transcriptomic, and metabolomic features 11,12 . Systematic studies have generated and integrated such large-scale datasets to characterize the landscape of metabolic pathway alterations and dependencies across cancer cell lines, demonstrating the context-specific nature of metabolic dependencies, and identifying new metabolic vulnerabilities in cancer cells [13][14][15][16][17][18] . Building upon promising outcomes from these studies, a critical next step would be to develop computational models that reveal metabolic state-specific gene or pathway co-dependencies to discover potential synthetic lethalities imposed by the cancer genotype or tissue context 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study found relationships between transcriptional regulator activity and metabolite levels, however, the associations were limited to 53 cancer cell lines 15 . On the other hand, numerous studies on cancer metabolism have solely used gene and protein expression to infer metabolic activity without direct profiling of metabolite levels 16–19 . However, gene expression patterns may not intuitively reflect the activity of metabolic pathways, 20 where the reaction rate or environmental factors may also have a substantial impact.…”
Section: Introductionmentioning
confidence: 99%
“…15 On the other hand, numerous studies on cancer metabolism have solely used gene and protein expression to infer metabolic activity without direct profiling of metabolite levels. [16][17][18][19] However, gene expression patterns may not intuitively reflect the activity of metabolic pathways, 20 where the reaction rate or environmental factors may also have a substantial impact. Another issue in previous cancer metabolism studies is that most research was focused on a specific cancer type [21][22][23][24] or metabolic pathway, 25,26 limiting a comprehensive understanding of metabolism reprogramming.…”
Section: Introductionmentioning
confidence: 99%